Exchange Rate Pass-Through to Inflation Via Trade Channel - Wijoyo, Daniel Satrio; Sugiyanto , Sugiyanto (Yayasan Riset dan Pengembangan Intelektual, 2024)
The rapid expansion of global trade and the volatility of currency exchange rates have a substantial impact on the stability and economic prosperity of a nation. This research is aims to observe the impact of the exchange rate pass-through (ERPT) to consumer inflation represent by consumer price index (CPI) via the trade channel that represent by the import price index (IPI), producer price index (PPI) and weighted exchange rate index represents by nominal effective exchange rate (NEER) during January 1997 to December 2021 for Indonesia’s study case. Along with the variance decomposition (VD) and impulse response function (IRF) methodologies, the study used the vector error correction model (VECM) and Johansen Cointegration procedures. These techniques were used to ascertain each variable shock's effect and its associated contribution in percentage. The study's results indicate that an increase in NEER, or the appreciation of the Rupiah, resulted in a decrease in consumer price, known as CPI. Conversely, an increase in prices via the trade channels, including IPI and PPI, resulted in a further increase in consumer price or CPI. Second, IPI has the highest contribution to the consumer price shocks followed by CPI itself, IPI and NEER during the observable period. Simultaneously, there are three observable different periods of the shocks that can be categorized based on the commonalities trend. First, huge fluctuation occurs from the start in the first month until the 15th month period. Second, the shock gradually stabilizes which starts in 15th month period until 30th month period. Finally, the shock experiences an incremental change towards the long-run equilibrium which starts after the 30th month period.